Methods Of Growing Current Plants - Ch. A. Anvarbekova; D.X. Ergasheva (Zien Journals, 2021)
Soil conditions for the vine. Planting and care of cuttings. Preparation of cuttings for planting. Propagation of vines by vegetative means from cuttings, green cuttings, grafting, pruning.
Keywords: Vine; soil; cuttings; vegetative